2012
DOI: 10.1002/prot.24216
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B inhibits the amyloid formation of human islet amyloid polypeptideand protects pancreatic beta‐cells against cytotoxicity

Abstract: The misfolding of human islet amyloid polypeptide (hIAPP) is regarded as one of the causative factors of type 2 diabetes mellitus (T2DM). Salvia miltiorrhiza (Danshen), one of the most commonly used of traditional Chinese medicines, is often used in Compound Recipes for treating diabetes, however with unclear mechanisms. Since salvianolic acid B (SalB) is the most abundant bioactive ingredient of salvia miltiorrhiza water-extract. In this study, we tested whether SalB has any effect on the amyloidogenicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…However, which compound from this extract is responsible for the antidiabetic effects is still unclear. In addition, a recent in vitro study (Cheng et al, 2013) has shown that SalB possessed the capacity to inhibit the formation of human islet armyloid polypeptide (hIAPP) amyloid and disaggregate hIAPP fibrils, and protected hIAPP-induced cytotoxicity on pancreatic INS-1 cells, which suggested a potential use of SalB for the treatment of diabetes. A systematic study, therefore, was required to verify the antidiabetic effects of SalB and to reveal its possible mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, which compound from this extract is responsible for the antidiabetic effects is still unclear. In addition, a recent in vitro study (Cheng et al, 2013) has shown that SalB possessed the capacity to inhibit the formation of human islet armyloid polypeptide (hIAPP) amyloid and disaggregate hIAPP fibrils, and protected hIAPP-induced cytotoxicity on pancreatic INS-1 cells, which suggested a potential use of SalB for the treatment of diabetes. A systematic study, therefore, was required to verify the antidiabetic effects of SalB and to reveal its possible mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting solutions were incubated under constant shaking at 25 C. For the disaggregation experiments, hIAPP monomers were rst incubated as described above for 24 h, which is sufficiently long for hIAPP to grow into mature brils. 45 Subsequently, equal volumes of brazilin solutions with different concentrations were added into the bril solutions. The resulting disaggregation solutions were incubated at 25 C under constant shaking.…”
Section: Aggregation and Disaggregation Experimentsmentioning
confidence: 99%
“…Our studies show that purified SAB from S. miltiorrhiza improves glucose tolerance supporting to the evidence that S. miltiorrhiza can be exploited further for its anti-diabetic properties. Based on our data and the existing literature, we acknowledge that multiple pathways for SAB action might be involved for its overall antihyperglycemic activity in vivo and there is evidence that SAB may reduce diabetes through its protective effect on pancreatic beta-cells [10].…”
Section: Discussionmentioning
confidence: 66%
“…Among phenolic acids, salvianolic acid B is a major component of S. miltiorrhiza and extensive pharmacological studies have been reported for this compound. Salvianolic acid B inhibited the amyloid formation of human islet amyloid polypeptide and protects pancreatic beta cells against cytotoxicity [10]. Many authors have studied the effect of salvianolic acid B on different organ systems in animals as well as in humans.…”
Section: Introductionmentioning
confidence: 99%